Aspirations for Higher Education of Youth in Kazakhstan based on Intersection of Gender and Disability - Manuilova, Natalya (Nazarbayev University Graduate School of Education, 2018)
Despite legislative action to develop inclusive education in Kazakhstan, the field of higher education has not received sufficient attention so far. This is arguably one of the reasons behind the low number of students with disabilities enrolled in higher education. To determine the factors influencing the decision of students to obtain higher education this qualitative study with phenomenology research design, explored the experience of 10 male and female students with various disabilities such as physical and sensory impairments, and different levels of education ranging from college graduates to PhD candidates. The intersection of participants’ gender and their disability, and its effect on educational and career choices of these students present an interesting research case. The outcomes of higher education were also analyzed in this study to identify the areas that require special attention at the current stage of higher education development to increase the number of students with disabilities in higher educational institutions of Kazakhstan. According to study participants, gender has no direct influence on their educational and career aspirations. However, analysis of their answers still revealed certain implicit gender restrictions. Gender, along with social and financial barriers, as well as the general inaccessibility of the environment for persons with disabilities, often has a negative impact on the formation of their aspirations. This may further limit students with special needs participation in the social life, as well as their career opportunities and professional development. Thus, higher education plays an important role in building general social justice and equality. This research offers recommendations for improving inclusive practices in higher education institutions of Kazakhstan.
Keywords: higher education; aspirations; disability; inclusion